2006
DOI: 10.17730/humo.65.1.4y2q0vhe4l30n0uj
|View full text |Cite
|
Sign up to set email alerts
|

Incorporating Fishermen’s Local Knowledge and Behavior into geographical information Systems (giS) for Designing marine Protected areas in Oceania

Abstract: Drawing on our experience in establishing marine protected areas (MPAs) in the Roviana and Vonavona Lagoons, New Georgia, Solomon Islands, this paper shows how a geographical information system (GIS) database can be used to incorporate sociospatial information, such as indigenous knowledge and artisanal fishing data, along with biophysical and other information to assist in MPA design. We argue that converting peoples' knowledge and socioecological behavior into geo-spatial data allows researchers to formulate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
120
0
5

Year Published

2011
2011
2021
2021

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 181 publications
(126 citation statements)
references
References 47 publications
1
120
0
5
Order By: Relevance
“…However, comparative studies have demonstrated that volunteer capabilities can be equal to professionals (e.g., Gillett et al 2012;Jordan et al 2012). In addition, some citizen science projects are designed specifically to tap into the expertise outside of professional science, as with collaborative fisheries research (Aswani and Lauer 2006;Dale and Armitage 2011) or ethnobotanical studies (Kimmerer 2012;Oguamanam 2004).…”
Section: Introductionmentioning
confidence: 99%
“…However, comparative studies have demonstrated that volunteer capabilities can be equal to professionals (e.g., Gillett et al 2012;Jordan et al 2012). In addition, some citizen science projects are designed specifically to tap into the expertise outside of professional science, as with collaborative fisheries research (Aswani and Lauer 2006;Dale and Armitage 2011) or ethnobotanical studies (Kimmerer 2012;Oguamanam 2004).…”
Section: Introductionmentioning
confidence: 99%
“…Australia, for example, is compiling and evaluating FEK for the purpose of better understanding long-term changes in fish stocks (AFMF 2006). For ecological issues that can be qualitatively described, e.g., vulnerable habitats, spawning aggregations, juvenile aggregations, or fish migration patterns, FEK can be directly incorporated into fishery management, such as in the placement of marine protected areas (MPAs; Aswani and Lauer 2006). This is especially relevant because a number of scientists view MPAs as a basic precautionary strategy for achieving both fishery management and conservation goals (Cooke andEarle 1993, Auster 2001).…”
Section: Discussionmentioning
confidence: 99%
“…However, these considerations should also be combined with broader contextual considerations stemming from the proactive use of social, economic, political, and natural scientific methods, tools, and approaches to design MPAs [11,[147][148][149]. For example, Aswani and Lauer [150] show how MPA networks can be designed using a combination of anthropological and natural scientific methods to merge traditional knowledge and use patterns in GIS. Ban et al [151] compare the use of Marxan planning software with a community-based approach to MPA planning on the west coast of Canada showing that both methods produced similar results.…”
Section: The Mpa Implementation and Design Processmentioning
confidence: 99%